Ammonia adsorption on nanostructured silica materials for hydrogen storage and other applications. - Thommes, Matthias; et al. (Journal of Nanoscience and Nanotechnology, 2008)
Our focus in the present study is to apply high sp. surface area SiO2 nanostructured porous materials (about 2,200 m2/g, as synthesized, and 600-700 m2/g, after stabilization) to adsorb NH3 for H storage and other chem. and pollution abatement applications. We describe here the synthesis, and characterization of these SiO2 materials, and the adsorption study of N2 and NH3. These materials were obtained with the help of a modification of the Stober-Fink-Bohn (SFB) method. The main change, made here to the SFB method, was the use of amines, i.e., triethylamine as catalysts instead of ammonium hydroxide. The SiO2 materials were characterized with the help of SEM and FTIR Spectrometry. The N2 adsorption study was carried out with the help of the Quantachrome-Autosorb-1 and the NH3 adsorption with the Quantachrome-Autosorb-1-C. The amt. of H adsorbed in the form of NH3 in the studied SiO2 samples at: P = 760 [Torr] (1.01325 × 105 [Pa]), was 2 [wt.%] and the amt. of H stored in the form of NH3 at about: P = 7500 [Torr] (10.0 × 105 [Pa]), in the studied stabilized SiO2 samples was 11 wt.%, a magnitude higher than the goal figure of 6.5 [wt.%] established by the United States of America, Department of Energy. [on SciFinder(R)]
Keywords: ammonia adsorption silica nanostructure hydrogen storage